Does Activating the Human Identity Improve Health-Related Behaviors During COVID-19?: A Social Identity Approach - Sparkman, David J.; Kleive, Kalei; Ngu, Emerson (Frontiers in Psychology, 2022)
Taking a social identity approach to health behaviors, this research examines whether experimentally “activating” the human identity is an effective public-health strategy to curb the spread of COVID-19. Three goals of the research include examining: (1) whether the human identity can be situationally activated using an experimental manipulation, (2) whether activating the human identity causally increases behavioral intentions to protect the self and others from COVID-19, and (3) whether activating the human identity causally increases behaviors that help protect vulnerable communities from COVID-19. Across two preregistered experiments (total N = 675), results suggest (1) the manipulation of identification with humanity had a significant but small effect on participants’ psychological bond with all humanity (Cohen’s ds = 0.21 – 0.27), but not their concern for all humanity. However, the manipulation had (2) no causal effect on health-related behavioral intentions or (3) helping behaviors that reduce the spread of COVID-19. Limitations, future directions, and direct benefits of the research are discussed.